1999
DOI: 10.1177/03635465990270060501
|View full text |Cite
|
Sign up to set email alerts
|

Eighteen- to Twenty-four-Year Follow-up After Complete Rupture of the Anterior Cruciate Ligament

Abstract: A unilateral, complete rupture of the anterior cruciate ligament was diagnosed in 60 consecutive patients by arthroscopy within 1 week of trauma. Most ruptured ligaments were treated by acute nonaugmented repair immediately after the arthroscopy. Fifty-five and 56 patients were reevaluated after 12 years and 20 years, respectively. Twenty-five patients (45%) had at least one reoperation during the follow-up period of 20 years, primarily for meniscal problems. Seven patients (13%) had repeat anterior cruciate l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
60
0
3

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(70 citation statements)
references
References 30 publications
6
60
0
3
Order By: Relevance
“…The long-term adaptation is not successful, neither in stable, reconstructed knees nor in chronic unstable knees, after failed reconstruction or with no reconstruction. This is in accordance with clinical data from subjective and quantitative functional assessment (Fremerey et al 2000, Bonfim et al 2003) of longterm follow-up in ACL injured knees (Maletius and Messner 1999).…”
Section: Discussionsupporting
confidence: 86%
“…The long-term adaptation is not successful, neither in stable, reconstructed knees nor in chronic unstable knees, after failed reconstruction or with no reconstruction. This is in accordance with clinical data from subjective and quantitative functional assessment (Fremerey et al 2000, Bonfim et al 2003) of longterm follow-up in ACL injured knees (Maletius and Messner 1999).…”
Section: Discussionsupporting
confidence: 86%
“…This high prevalence makes it impossible to determine the combined versus the individual effects of ACL tears and meniscal tears on OA outcomes. Indeed, many of these meniscal tears probably occurred months to years after the original ACL injury (27,28). We have also previously reported that in this sample, meniscal tears have no association with OA pain severity (29).…”
Section: Discussionmentioning
confidence: 56%
“…The current study made statistical comparisons of 24 hip (9). knee (9) and ankle (6) dependent measures, between both genders (2) and movements (3). A power analysis revealed that to achieve 80% statistical power in the current study with an exploratory alpha level of 0.05, a minimum of eight subjects per group (male and female) were required.…”
Section: Subjectsmentioning
confidence: 93%